2001
DOI: 10.1016/s0885-3924(00)00264-5
|View full text |Cite
|
Sign up to set email alerts
|

An Attempt to Employ the Zung Self-Rating Depression Scale as a “Lab Test” to Trigger Follow-Up in Ambulatory Oncology Clinics

Abstract: We examined issues of criterion validity and detection of depression employing the Zung Self-Rating Depression Scale (ZSDS) as a "lab test" to trigger follow-up interviews of ambulatory oncology patients by oncology staff and the possibility of subsequent algorithm-based antidepressant treatment. Sixty oncology patients were screened with the ZSDS and then interviewed using the Mini-International Neuropsychiatric Interview (MINI). We examined the sensitivity and specificity of various cutoffs on the ZSDS and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 18 publications
2
35
0
3
Order By: Relevance
“…Scores range from 20 to 80, with higher scores reflecting more depressive symptoms. Passik et al (2001) reported a coefficient alpha of .84. The coefficient alpha in the present study was .85.…”
Section: Methodsmentioning
confidence: 99%
“…Scores range from 20 to 80, with higher scores reflecting more depressive symptoms. Passik et al (2001) reported a coefficient alpha of .84. The coefficient alpha in the present study was .85.…”
Section: Methodsmentioning
confidence: 99%
“…[1] However, far less than 30% of cancer patients showing psychosocial problems are recognized in clinical settings by oncologists and thus referred to proper sources of psychological support [2,3]. Several psychometric instruments, such as the Hospital and Anxiety Depression Scale (HADS) [4][5][6], the Brief Symptom Inventory (BSI) [7], the Profile of Mood States (POMS) [8], and the Zung Depression Inventory [9] have been suggested as clinical tools to be routinely used in cancer settings in order to improve the detection of psychosocial morbidity, especially depression, and the referral of patients who resulted as "cases" [10,11]. Lack of time and lack of self-confidence in exploring psychosocial dimensions and in using psychometric instruments have been raised by cancer physicians as the most frequent barriers for not detecting and referring patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…Depression screening tests that have demonstrated beneft in oncology patients include the Patient Health Questionnaire, 37 the Zung Depression Scale, 38 and the Beck Depression Inventory. 39 Te Hospital Anxiety and Depression Scale is an efcient and commonly used screening tool for anxiety among cancer patients and can also help screen for depression.…”
Section: Reviewmentioning
confidence: 99%